2002
DOI: 10.1002/glia.10092
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐specific gene expression in early differentiating oligodendrocytes

Abstract: The screening of a differential library from precursor and differentiated oligodendrocytes, obtained through the representational difference analysis (RDA) technique, has generated a number of cDNA recombinants corresponding to mRNA coding for known and unknown proteins: (1) mRNA coding for proteins involved in protein synthesis, (2) mRNA coding for proteins involved in the organization of the cytoskeleton, and (3) mRNA coding for proteins of unknown function. The expression profile of the mRNA was studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Ribosomal proteins are closely involved with replication, transcription, DNA repair, RNA processing, regulation of development and malignant transformation (Blasi et al 2002). Transcriptional regulation of ribosomal protein expression is an important mechanism in controlling ribosome assembly and function (Posas et al 2000).…”
Section: Results Of Blastx Number Of Estsmentioning
confidence: 99%
“…Ribosomal proteins are closely involved with replication, transcription, DNA repair, RNA processing, regulation of development and malignant transformation (Blasi et al 2002). Transcriptional regulation of ribosomal protein expression is an important mechanism in controlling ribosome assembly and function (Posas et al 2000).…”
Section: Results Of Blastx Number Of Estsmentioning
confidence: 99%
“…Interestingly, catalytically inactive S478A tPA was able to restore microglial activation equally well both in vivo and in culture, a result that argued for a catalytically independent cytokine function for tPA on microglia. Further experiments identified tPA as a product deriving from both excitotoxintreated neurons and activated microglia, and indicated that tPA of both neuronal and microglial origin is necessary to activate naïve microglia (Siao and Tsirka, Rosenblatt et al (1987); 12 Blasi et al (2002); 13 Mulligan et al (1991). 2002). The cytokine activity was attributed to the Nterminal fibronectin type III finger domain of tPA.…”
Section: Tpa and Microglial Functionmentioning
confidence: 96%
“…The resulting vector was named pET-15b-PN-1. Polyclonal antiserum was raised in rabbit against affinity purified His-tagged PN-1 [21].…”
Section: Construction Of Rat Pn-1 Vectorsmentioning
confidence: 99%
“…Subconfluent cells on glass cover slips, were fixed with cold 3.7% formaldehyde (Fluka, France) in PBS with Ca 2+ (0.1 g/l) and Mg 2+ (0.1 g/l) for 20 min, permeabilized with 0.1% Triton X-100 in PBS for 5 min. The cover slips were incubated for 2 h at room temperature with polyclonal PN-1 antibodies [21] at a 1:20 dilution in a PBS-0.2% gelatin solution, washed three times for 5 min with 0.5 M NaCl, 0.02 M Sodium phosphate buffer pH 7.4 and finally, with PBS. An anti-rabbit IgG (Fc-specific) fluorescein-isothiocyanate (FITC)-conjugated (Jackson Immunoresearch Laboratories) was used as secondary antibody, at 1:200 dilutions in PBS-0.2% gelatin, for 1 h at room temperature.…”
Section: Cell Cultures Dna Transfections and Immunocytochemistrymentioning
confidence: 99%